Two faces of globalization munificent and malevolent - Das, Dilip K. 1945- (Edward Elgar, 2009)
"Like the ancient Roman god Janus, globalization has two faces, one benign and the other malign. In this comprehensive and authoritative book, Dilip K. Das fills a gap in the literature by examining both aspects of the contemporary phase of economic globalization." "Because globalization has had both welfare-enhancing, propitious consequences as well as detrimental ones, it has become an acutely contentious subject among the scholarly and public policy-making communities. Contemporary globalization cannot be studied without a balanced treatment of both facets. The author provides precisely that, covering large thematic areas of the global economy and globalization through the channels of trade, financial flows and attention to newly emerging trends, as well as including historical perspectives." "Neither overly technical nor highly model-oriented, this accessible book will be of great interest to scholars, students and other readers interested in a broad and balanced view of globalization."--BOOK JACKET.